The equation x^2 + y^2 - 6x + 10y + 9 = 0 has to be expressed in the form (x-a)^2 + (y-b)^2 = r^2

x^2 + y^2 - 6x + 10y + 9 = 0

=> x^2 - 6x + 9 + y^2 + 10y + 25 = -9...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The equation x^2 + y^2 - 6x + 10y + 9 = 0 has to be expressed in the form (x-a)^2 + (y-b)^2 = r^2

x^2 + y^2 - 6x + 10y + 9 = 0

=> x^2 - 6x + 9 + y^2 + 10y + 25 = -9 + 9 + 25

=> (x - 3)^2 + (y + 5)^2 = 5^2

**The center of the circle represented by x^2 + y^2 - 6x + 10y + 9 = 0 is (3, -5) and the radius is 5.**